2013
DOI: 10.1007/s11357-012-9498-3
|View full text |Cite
|
Sign up to set email alerts
|

β1-Adrenergic receptor blockade extends the life span of Drosophila and long-lived mice

Abstract: Chronic treatment with β-adrenergic receptor (βAR) agonists increases mortality and morbidity while βAR antagonists (β-blockers) decrease allcause mortality for those at risk of cardiac disease. Levels of sympathetic nervous system βAR agonists and βAR activity increase with age, and this increase may hasten the development of age-related mortality.Here, we show that β-blockers extend the life span of healthy metazoans. The β-blockers metoprolol and nebivolol, administered in food daily beginning at 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 56 publications
(75 reference statements)
4
39
0
Order By: Relevance
“…These results suggest that screening drugs and supplements in lower eucaryotes may be confounded by high false discovery rates. However, our experience has been that many compounds which extend mouse lifespan also extend the lifespan of Drosophila (e.g., Spindler et al 2013c). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that screening drugs and supplements in lower eucaryotes may be confounded by high false discovery rates. However, our experience has been that many compounds which extend mouse lifespan also extend the lifespan of Drosophila (e.g., Spindler et al 2013c). …”
Section: Discussionmentioning
confidence: 99%
“…Second, therapeutics may have both negative and positive effects on lifespan and healthspan. Beginning treatment at a later age may reduce the accumulated toxic effects of a potential therapeutic (Spindler et al 2013c). Third, rapamycin, the most efficacious model therapeutic yet found in mice, is approximately equally effective whether administration is begun at 9 or 20 months of age (Miller et al 2011).…”
Section: Effects On Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the β-blockers, it was recently reported that metoprolol and nebivolol extend the lifespan of mice 21) . It has been hypothesized that this lifespan extension effect is the result of an off-target effect different from that of the original target molecule of the drug.…”
Section: Hyperlipidemic Drugsmentioning
confidence: 99%
“…The versatility of taurine thus makes it a promising CRM candidate compound. Notably, taurine has already been shown to reduce tunicamycin-induced endoplasmic reticulum stress and extend the lifespan of lower organisms (C. elegans) 44) , offering further promise as a CRM for higher Telmisartan Antihypertensive AT1 possible 20) Metoprolol Antihypertensive ACE yes 21) Rapamycin Immunosuppressive mTOR yes 22) Rikkunshito Neuropeptide Y activator GHS-R yes 33) Taurine Anti-congestive heart failure various yes 44) 205 JPFSM : Effects of calorie restriction mimetics organisms. Table 1 provides a summary of the CRM candidates described in this review that are currently in clinical use or being clinically trialed for various age-related diseases.…”
Section: Taurinementioning
confidence: 99%